Pasubaya Mawarang in Marriage at Gelahang: A Review Based on Balinese Customary Law - Krishna Satrya Nugraha Taira,; Made Warka,; Tomy Michael, (Technium Social Sciences Journal, 2025)
In the teachings of Catur Asrama wiwaha is included in Grehastha Asrama, According to Law No. 1 of 1974 article 1 it is explained: Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the Almighty God. Wiwaha in Hinduism is seen as something very noble, as explained in the Manawa Dharma Sastra book that the wiwaha is sacred and the law is mandatory, in the sense that it must be carried out by a normal person and as an obligation in his life. The main purpose of wiwaha is to obtain offspring or sentana, especially the suputra. It is further explained in the Manawa Dharmasastra Book that wiwaha is the same as Samskara (Wiwaha Samskara), which places the position of marriage as an institution that has a close relationship with the Hindu religion. The wiwaha ceremony is the peak of Manusa Yadnya, as a self-purification ceremony (Sarira Samskara). In addition, the wiwaha ceremony must be guided by and follow the conditions that have been determined in Hindu law. Legally, the legal basis for marriage in Gelahang is a verse in Manawa Dharmasastra IX. 118 which regulates women's inheritance rights, although it is also stated that men are the heirs. The verse that states that women have the right to inherit is as follows: "Svebhyom sebhyastu kanya Bhyah pradadyur bhratarah prthak Svat svadamsac caturbhagam Patitah syuraditsavah". This means "but to female relatives, the brothers will give some of their portions, each one a quarter of their portion; those who refuse to give it will be ostracized.